In search of the spirit : the living national treasures of Japan - Hamanaka Sheila; Ohmi Ayano (New York : Morrow Junior Books, 1999)
Describes the creations of some of Japan's Living National Treasures, artists who are involved in various Japanese arts, including Yuzen dyeing, bamboo basket weaving, Bunraku puppetmaking, swordmaking, Noh theater, and neriage ceramics.
ALA Notable Book, 2000.
Notable Children's Trade Book in the Field of Social Studies, 2000.
Keywords: Arts Japanese -- Juvenile literature; Artists -- Japan -- Biography -- Juvenile literature; Japan -- Biography -- Juvenile literature